Virtual Instrument of Harmonics Detection Based on Neural Network Adaptive Filters - Xianfeng Zheng; Zheng Fan (Universitas Ahmad Dahlan, 2015)
This study investigated the adaptive detection principle based on a single artificial neuron, and constructed a method for detecting harmonics using the artificial neural network technique. Based on the established method, and by comprehensively processing the obtained harmonics data using the LabVIEW software-developing environment of the virtual instrument, the harmonic waves were detected and analyzed. Finally, the analysis of current ball crusher harmonics verified that the designed system was effective.